Understanding the microstructural evolution of cold sprayed Ti-6Al-4V coatings on Ti-6Al-4V substrates - Lek, Jun Yan (2020)
Rapid development of cold spray technology has made it a viable option to remanufacture and repair damaged engineering components made of Ti-6Al-4V (Ti64). This solid-state deposition process contributes to the distinctive microstructure of Ti64 coatings. In this study, the microstructural evolution of Ti64 from feedstock powder to coating as a result of high strain rate deformation is evaluated. TEM lamellae were extracted from the particle-substrate and particle-particle interfaces of a cold sprayed coating by focused ion beam milling and a comprehensive microstructural analysis was carried out. The feedstock powder is predominantly composed of martensitic lathes. The microstructure of the coating at the particle-substrate interface is noticeably different from the microstructure of the feedstock powder. Narrow regions consisting of nanometre-sized grains are observed in both the particle and substrate in the vicinity of the interface. Adiabatic shear instability under localized high strain rate deformation and heat accumulation are believed to be responsible for this observation. However, the martensitic structure is partially retained in the less deformed region of the particles, further away from the interfaces. The formation mechanism of the microstructure observed from the inner region of particle, at the vicinity of the particle-substrate and particle-particle interfaces respectively is discussed in the light of microstructural observations and finite element modelling.